2022
DOI: 10.23971/jefl.v12i2.3941
|View full text |Cite
|
Sign up to set email alerts
|

Code-switching in EFL classrooms: factors influencing teachers to use code-switching and its types used in the classrooms

Abstract: Among myriad prior studies on code-switching, little has been done on the factors influencing teachers to use code-switching and their classroom practices. The current research was aimed at investigating the motives of EFL teachers applying code-switching and the sorts of code-switching used by the EFL teachers in the classroom. This study used a qualitative case study as a research design by conducting in-depth interviews and observations as a data collection process. The obtained data were analyzed through c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…The cooperating teacher switched his language from English to Sinugbuanong Binisaya at level of clause or sentence, which adheres that only bilinguals with high levels of fluency are able to switch in this way, which appears to involve unique rules governing how the syntax and morphology of both languages may interact. In which Murtiningsih et al (2022) mentioned that fluency in bilinguals usually has an impact on intrasentential switching. By switching between English and Sinugbuanong Binisaya in a sentence, it demonstrated the significance of complementary functions.…”
Section: Extract 1: L15mentioning
confidence: 99%
“…The cooperating teacher switched his language from English to Sinugbuanong Binisaya at level of clause or sentence, which adheres that only bilinguals with high levels of fluency are able to switch in this way, which appears to involve unique rules governing how the syntax and morphology of both languages may interact. In which Murtiningsih et al (2022) mentioned that fluency in bilinguals usually has an impact on intrasentential switching. By switching between English and Sinugbuanong Binisaya in a sentence, it demonstrated the significance of complementary functions.…”
Section: Extract 1: L15mentioning
confidence: 99%
“…As a result, they offered suggestions for how to include some aspects of native languages in educational classroom instruction. Some literature indicated that the switching of codes improves learning and instruction in academic subjects (Hussein, Saed & Haider 2020;Kusumo Adi & Ambarini 2022;Murtiningsih et al 2022;Razak & Shah 2020). Teachers frequently establish an accepting atmosphere for communicating with learners of the English language in the senior phase even if they frequently employ code-switching to teach substantive subjects in the educational setting.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Ahmad, Mahmood and Shahid (2023) posit that codeswitching is the alternate usage of multiple languages in the same conversation; for example, a phrase could start in a particular language, and then conclude in a different one. On the other hand, Murtiningsih, Munawaroh and Hidayatulloh (2022) alluded to the point that code-switching is thought to be utilised not just in distinct languages but also in dialects and forms of the exact vocabulary. While tests are administered in English, majority of South African schools, particularly those in the Eastern Cape province study subjects such as Natural Science in both English and isiXhosa (Sibanda 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have explored the use of CS in the English teaching and learning process. Murtiningsih et al (2022) endeavored to investigate the teachers' motives and types of CS employed by teachers. They pinpointed five motives behind teachers' utilization of CS and observed three types of CS, which are inter-sentential switching, intra-sentential switching, and tag-switching.…”
Section: Introductionmentioning
confidence: 99%